Variation in virulence in the rice blast fungus Magnaporthe grisea in São Paulo State - Urashima, Alfredo Seiiti (Pesquisa Agropecuaria Brasileira, 2002)
Resistant varieties have been the preferred means to control Magnaporthe grisea, the causal organism of the rice blast disease. The objective of this study was to examine the degree of diversity of the pathogen in different rice growing regions of São Paulo State, Brazil. Blast samples collected from rice varieties in three different regions (Tremembé, Mococa and José Bonifácio) were analyzed for race structure employing the Japanese rice differentials. The highest degree of virulence diversity was observed in Tremembé with 22 different races in three different varieties. Furthermore, no resistance gene in the Japanese differentials was effective to all isolates of M. grisea from São Paulo State.